Subconjunctival Bevacizumab as an Adjunct to 5-Fluorouracil Enhanced Trabeculectomy: Short Term Results - Nadeem, Sana (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare the results of trabeculectomy with subconjunctival Bevacizumab and 5-Fluorouracil (5-FU); with trabeculectomy with 5-Fluorouracil alone in the short term (i.e. 3 months). Study Design: Prospective, interventional study Place and Duration of Study: Department of Ophthalmology, Fauji Foundation Hospital, Rawalpindi, from 18th December 2013 till 16th August 2018. Material and Methods: A total of 30 eyes (15 in each group) in patients above 40 years of age with primary glaucoma, underwent trabeculectomy with 5-Fluorouracil (5-FU) (50 mg/ml) applied for 5 minutes. At the end of surgery, sub-conjunctival Bevacizumab (Avastin® 2.5 mg in 0.1 ml) was injected in one group. The postoperative IOP, bleb configuration, and complications at 1 day, 1 week, 1 month, and then monthly for 3 months was observed for both groups. Results: The mean pre-operative IOP in the 5-FU group was 30.6 ± 17.1 mm Hg compared to 28.9 ± 18.9 mm Hg in the 5-FU + Bevacizumab group. The mean IOP of the 5-FU group at 3 months was 13.8 ± 4.25 mm Hg, compared to 12.5 ± 3.37 mm Hg in 5-FU + Bevacizumab group, Comparison of the mean IOP between the two groups revealed lower mean IOP in the 5-FU group at Day 1 (p = 0.556) , week 1 (p = 0.872), and month 1 (p = 0.042), but higher at month 3 (p = 0.339). Bleb morphology between the two groups was statistically insignificant (p = 0.405). Conclusion: There is no added benefit of subconjunctival Bevacizumab used as an adjunct to 5-FU enhanced trabeculectomy in the short term. Key Words: Trabeculectomy, 5-Fluorouracil, Bevacizumab, glaucoma, intraocular pressure.